Interwrapping Distinct Metal-Organic Frameworks in Dual-MOFs for the Creation of Unique Composite Catalysts - Jia-Long Ling; Kai Chen; Chuan-De Wu (Research, 2021)
Incorporating metal nanoparticles (MNPs) inside metal-organic frameworks (MOFs) demonstrates superior catalytic properties in numerous reactions; however, the size and distribution of MNPs could not be well controlled, resulting in low product selectivity in catalysis by undergoing different catalytic reaction pathways. We report herein a facile strategy for integrating lattice-mismatched MOFs together to fabricate homogeneously distributed “dual-MOFs,” which are the ideal precursors for the preparation of MNPs@MOFs with unique catalytic properties. As a proof of concept, we successfully synthesize a dual-MOF HKUST-1/ZIF-8 for in situ creation of redox-active Cu NPs inside hierarchical porous ZIF-8 under controlled pyrolytic conditions. Combining the advantages of size-tunable Cu NPs in the molecular sieving matrix of ZIF-8, Cu@ZIF-8 demonstrates high activity and selectivity for transformation of alkynes into alkenes without overhydrogenation, which surpasses most of the catalysts in the literature. Therefore, this work paves a new pathway for developing highly efficient and selective heterogeneous catalysts to produce highly value-added chemicals.